2013
DOI: 10.1016/j.ijscr.2013.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma at an ileostomy site—Fifty-four years following colectomy for ulcerative colitis: A case report and literature review

Abstract: Patients with chronic stomal inflammation, bleeding or persistent induration and/or mass formation should be followed up closely and investigated for recurrence or development of a new malignancy. There should be a low threshold to obtain an early definitive tissue diagnosis by taking biopsies to prevent local or systemic invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…A patch test excluded a contact dermatitis to any of the components of the stoma pouch material or to other related accessories and cleansing products. Even if carcinoma arising at an ileostomy is a rare occurrence [1] , we performed biopsies on the glandular mucosa on the external side of the stoma, which confirmed the absence of any dysplastic change or malignancy. Histology confirmed the presence of florid inflammation and ulceration with fibrino-purulent slough, in keeping with severe ileitis also with ulcerative changes ( Fig.…”
mentioning
confidence: 75%
“…A patch test excluded a contact dermatitis to any of the components of the stoma pouch material or to other related accessories and cleansing products. Even if carcinoma arising at an ileostomy is a rare occurrence [1] , we performed biopsies on the glandular mucosa on the external side of the stoma, which confirmed the absence of any dysplastic change or malignancy. Histology confirmed the presence of florid inflammation and ulceration with fibrino-purulent slough, in keeping with severe ileitis also with ulcerative changes ( Fig.…”
mentioning
confidence: 75%
“…Primary squamous cell carcinoma at the ileostomy site is an extremely rare tumor. Literature search including PubMed, Google, and Medline, yielded only 6 reported cases prior to our report 1 …”
Section: Discussionmentioning
confidence: 99%
“…They found only three cases reported, including the one they presented. Since then, Farshid and colleagues published a case report and another literature review in which they reported a total of 6 cases of SCC at the ileostomy site 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations